Mangrove Rhizosphere Soils: A Unique Natural Source of Pravastatin-Producing Penicillium Microfungi - N., Zainol; Emine, Seydametova; Jailani, Salihon; Convey, Peter (SRET, 2015)
The pravastatin-producing potential of rhizosphere soil microorganisms from mangrove forests has not been investigated in detail. In this study, a total of 20 Penicillium isolates were tested for pravastatin production. Six strains were able to synthesize pravastatin directly. Among these, the isolate Penicillium sp. ESF19M was the most active pravastatin producer with a yield of 28.43 mg/L. Molecular identification of this strain showed the highest homology with Penicillium citrinum.